2018
DOI: 10.11113/sh.v10n3-3.1520
|View full text |Cite
|
Sign up to set email alerts
|

Kesediaan, Penerimaan Dan Pengoperasian Guru Reka Bentuk dan Teknologi Terhadap Amalan dalam Pentaksiran Berasaskan Sekolah

Abstract: This study aims to identify the readiness, acceptance and operation of Design and Technology teachers on Practice in School-Based Assessment (PBS). PBS is a holistic assessment that assesses cognitive (intellectual), affective (emotional and spiritual) aspects and psychomotor (physical) in line with the National Education Standard and Primary School Curriculum (KSSR) Philosophy. This study aims to examine the implementation of PS practices on Design and Technology teachers in national schools in the southern s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The effect of AL compared to conventional methods in Wiliawanto et al (2019) study proves that AL is highly efficient in enhancing students' understanding of a subject and can subsequently help improve student performance in those subjects. Studies by Moktar et al (2018) have found that students' continuous development from time to time in the classroom may be identified via the application of AL as well as systematic classroom evaluation. Thus, learning techniques that are not in line with the development of the latest technology and are not student-centered will end up in poor exam results (Hui et al, 2021).…”
Section: Active Learning and Student Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of AL compared to conventional methods in Wiliawanto et al (2019) study proves that AL is highly efficient in enhancing students' understanding of a subject and can subsequently help improve student performance in those subjects. Studies by Moktar et al (2018) have found that students' continuous development from time to time in the classroom may be identified via the application of AL as well as systematic classroom evaluation. Thus, learning techniques that are not in line with the development of the latest technology and are not student-centered will end up in poor exam results (Hui et al, 2021).…”
Section: Active Learning and Student Achievementmentioning
confidence: 99%
“…Taking into consideration the usage of active learning, this way of teaching and learning has a necessary importance in the 21st century (Moktar et al, 2018). However, we were unable to locate any scales or instruments that directly evaluated learners' active learning practices in specific business subject related field.…”
Section: Introductionmentioning
confidence: 95%
“…The Standard Based Curriculum for Secondary School (KSSM), was executed in 2017 to replace the Integrated Secondary School Curriculum (KBSM) (Moktar et al, 2018). Reka Bentuk dan Teknologi (RBT) is the latest addition in the curriculum.…”
Section: Design and Technology (Reka Bentuk Dan Teknologi)mentioning
confidence: 99%
“…Therefore, to ensure that the Malaysian education system continues to be relevant in a rapidly developing world, a combination of innovation and creativity in the education system and through concerted efforts and changes on all sides, the ever-changing challenges of the 21st century can be overcome [4]. Therefore, this study was carried out to identify the effect of computerized electronic circuit simulation on the performance, motivation and motivation of students in RBT subjects in secondary schools to facilitate students to read, interpret and transfer wiring circuits to schematic circuits that are able to contribute to skilled personnel in the field of technology.…”
Section: Introductionmentioning
confidence: 99%